The Academic Scientist’s Commitment to Epistemic Responsibility - Bor Luen Tang (Philosophies)
Questionable research practices (QRPs) and research misconduct (RM) involving university scientists waste resources and erode public trust in science and academia. Theories put forth for the occurrence of these transgressions have ranged conceptually from that of errant individuals (“bad apple”) to an environment/culture which is conducive for, if not promotive of, QRP/RM (“bad barrel”), or a combination of both. These ideas appear to provide explanations for lapses in epistemic responsibility and offer reasons for instances of transgression. Some have even argued that scientific conclusions need not be accurate, justified, or believed by their authors. I take the opposite view and instead argue that academic research should be carried out such that a scientist’s fundamental commitment to their epistemic responsibility triumphs over all reasons and incentives to err. In other words, carrying out and publishing research in which the results are authentic and veracious to the best of the scientist’s knowledge and ability should be a default state of mind, a preferred path of action, or a moral axiom. This is a notion that should permeate any courses on research ethics and integrity.